2018
DOI: 10.1021/acs.energyfuels.8b01608
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Influencing Factors for Forced Imbibition in Tight Sandstone Based on Low-Field Nuclear Magnetic Resonance Measurements

Abstract: Spontaneous imbibition (SI) generally occurs under forced pressure (the difference between hydraulic fluid pressure and original pore pressure) during shut-in time. However, the experimental study of SI is commonly performed at atmospheric pressure and the effect of the forced pressure is often neglected. How the forced pressure influences the SI behaviors under different factors is still not clear. In this paper, low-field nuclear magnetic resonance (LF-NMR) was adopted to study the mechanism of SI in the tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…However, according to the pattern of spontaneous imbibition, all boundary conditions can be divided into two categories, i.e., all open faces covered by water ( Fig. 1a) (Xu et al, 2018) and part of open faces covered by water ( Fig. 1b) (Harimi et al, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the pattern of spontaneous imbibition, all boundary conditions can be divided into two categories, i.e., all open faces covered by water ( Fig. 1a) (Xu et al, 2018) and part of open faces covered by water ( Fig. 1b) (Harimi et al, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 Adding surfactants to the fracturing fluid to change the wettability and reduce the interfacial tension can effectively improve the oil recovery after fracturing reformation. 25 30 Based on the mass method experiment, it was found that the degree of salinity is negatively correlated with spontaneous imbibition recovery; 31 , 32 fractures can effectively expand the imbibition area of the dense matrix in contact with water, thereby increasing the recovery and imbibition rate. 33 Guo and Ren noted that there is a certain optimal interfacial tension that reduces the amount of bypassed oil in the formation, resulting in the highest imbibition recovery, rather than a lower interfacial tension corresponding to the higher oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The pore throat radius of tight oil reservoirs is on the nanometer scale and the thickness of the adsorption layer is on the micron scale. Pores above the submicron scale play a leading role in the process of oil displacement in tight reservoirs owing to the thickness of the adsorption layer, and nano-submicron pores contribute less to imbibition recovery . In cores with different pore structure combinations, the ratio of medium to large pore throats determines the effect of spontaneous imbibition and oil displacement; residual oil is mainly retained in the microporous throats. , Cheng, Lai et al investigated the influence of gravity and pore throat structure on the imbibition effect during the imbibition process and noted that the nanopore throat is the main imbibition point. , In previous studies, scholars have mainly used the mass and volume methods to conduct imbibition experiments, exploring the factors that affect imbibition and displacement; however, these experiments were mostly based on formation water. , Adding surfactants to the fracturing fluid to change the wettability and reduce the interfacial tension can effectively improve the oil recovery after fracturing reformation. Based on the mass method experiment, it was found that the degree of salinity is negatively correlated with spontaneous imbibition recovery; , fractures can effectively expand the imbibition area of the dense matrix in contact with water, thereby increasing the recovery and imbibition rate . Guo and Ren noted that there is a certain optimal interfacial tension that reduces the amount of bypassed oil in the formation, resulting in the highest imbibition recovery, rather than a lower interfacial tension corresponding to the higher oil recovery. , Jing et al studied the influence of matrix permeability, temperature, pressure, pore size, and fracture density on the degree of dynamic imbibition production; a normalized model of the dimensionless imbibition recovery degree is obtained using dimensionless experimental parameters .…”
Section: Introductionmentioning
confidence: 99%
“…As a key unconventional energy, tight oil has received increased attention by many scholars and has gradually become another research topic following shale gas [1]. The commercial exploitation of tight oil has greatly affected the energy structure of the world, especially North America [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…After hydraulic fracturing stimulation, shut in operations for a period are beneficial to the production increase of tight oil. Extended shut in time can promote fracturing fluid imbibition into reservoirs to displace crude oil and has been proven to be effective for enhanced oil recovery [1].…”
Section: Introductionmentioning
confidence: 99%